Pemetaan Daerah Rawan Longsor di Kecamatan Banyumanik, Kota Semarang - Ubaidillah, Taqorrub; Mufidah, Nastiti (IJTIMAIYA: Journal of Social Science and Teaching, 2021)
The research was done in Banyumanik Sub-district, Semarang City, Central Java Province. The purposes of the research were to know terrain unit and landslide suceptibility in the research area. Unit of analysis in this research was terrain unit which obtained from overlay between landform, geology, slope, and soil maps. The overlay result is 147 terrain units in the research area. Sampling technique use stratified random sampling to select sample based strata. 19 samples are selected from 147 terrain units. Method of collecting data use survey method to obtain primary data and documentation method to obtain secondary data. Technique of data analysis use wight method for 6 parameters. The parameters are land use, soil tecture, rock layering structure, rainfall, soil permeability and slope. Research results show that landslide susceptibility in the research area was classified in 5 susceptibility classes i.e. very low class cover area of 0,6 km2 (0,19%), low class cover area of 7,24 km2 (23,59%), moderate class cover area of 7,16 km2 (23,33%), high class cover area of 12,35 km2 (40,24%), and very high class cover area of 3,88 km2 (12,64%).